A Functionally Graded Cathode Architecture for Extending the Cycle‐Life of Potassium‐Oxygen Batteries. Issue 8 (10th May 2019) - Gilmore, Paul; Sundaresan, Vishnu B.
Abstract: Potassium‐Oxygen (K−O2 ) batteries have a high theoretical energy density of 935 Wh kg −1 due to a single‐electron redox process in the reversible formation of potassium superoxide. Despite this advantage, standard K−O2 batteries have limited cycle‐life (5‐10) due to molecular oxygen crossover from cathode to anode, resulting in side reactions forming undesired superoxide on the anode. In this article, a K−O2 battery fabricated with a functionally‐graded cathode (FGC) architecture is presented to address oxygen crossover at the cathode. This K−O2 battery lasts >125 cycles with minimal loss in coulombic efficiency when charged/discharged to 300 μAh (238 μAh cm −2 ). The FGC is comprised of a carbon fiber layer, microporous carbon and polypyrrole doped with hexafluorophosphate. It provides a scalable architecture for regulating K + ion and oxygen transport at the cathode trilayer (liquid‐solid‐air) interface. The PPy(PF6 ) formed on the cathode is observed to have an ORR rate two orders greater than that of carbon‐based electrodes, as it promotes the reversible formation of potassium superoxide at the cathode, minimizes the transport of molecular oxygen into the electrolyte, and subsequently improves anode stability and cycle‐life of the K−O2 battery. These improvements in performance with FGC come at a marginal increase in K−O2 battery material cost, which is estimated to be 44 kWh −1 . The combination of performance and cost kWh −1 makes this architecture the most cost‐effective electrochemical energy storage device for stationary applications. Abstract : Make the grade : due to the crossover of molecular oxygen from cathode to anode, K−O2 batteries usually show a very limited cycle‐life. To address this issue, a K−O2 battery fabricated with a functionally‐graded cathode (FGC) architecture is presented, which lasts >125 cycles with minimal loss in coulombic efficiency. The combination of performance and cost kWh −1 renders this architecture as a promising candidate for electrochemical energy storage devices for stationary applications.